2020
DOI: 10.1038/s42003-020-01457-4
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation during sleep with incomplete reminder cues rather than complete ones stabilizes long-term memory in humans

Abstract: Reactivation by reminder cues labilizes memories during wakefulness, requiring reconsolidation to persist. In contrast, during sleep, cued reactivation seems to directly stabilize memories. In reconsolidation, incomplete reminders are more effective in reactivating memories than complete reminders by inducing a mismatch, i.e. a discrepancy between expected and actual events. Whether mismatch is likewise detected during sleep is unclear. Here we test whether cued reactivation during sleep is more effective for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 79 publications
5
24
0
Order By: Relevance
“…In conclusion, our present results not only support previous data showing that targeted memory reactivations can be implemented in real-life settings 14 but also showed that complex information such as that of a history lesson can be associated with an odor in the classroom and that its consolidation can be improved with just one session of reactivation during the first night of sleep in the students’ homes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, our present results not only support previous data showing that targeted memory reactivations can be implemented in real-life settings 14 but also showed that complex information such as that of a history lesson can be associated with an odor in the classroom and that its consolidation can be improved with just one session of reactivation during the first night of sleep in the students’ homes.…”
Section: Discussionsupporting
confidence: 90%
“…odor or sound) previously linked to a task (e.g. word pairs) is presented again during sleep, particularly during the first Non-Rapid Eye Movement (NREM) sleep cycles, memory strengthening and/or protection against interferences emerges as a result of the induced reactivation 3 , 11 14 . Thus, the presentation of specific cues during learning and subsequent sleep could guide which content would be consolidated in the sleeping brain (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cues that involve a discrepancy between what is expected and what actually occurs (Prediction Error), are proposed to drive memory reactivationreconsolidation (26). A recent work by Forcato and colleagues (38) provided evidence that only reminders that included a prediction error (incomplete reminders) stabilized memory in the long term. We believe that our Reactivation-based intervention followed similar principles in the "reminder" construction and thus promoted memory strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation Intervention. Based on our previous work and sleep studies (20,27,28,38), we constructed incomplete reminders in order to reactivate the stabilized memory acquired on Day 1. This type of reactivation session was demonstrated to have superior effects on episodic memory retention than other types of reactivation.…”
Section: Day 2 (Memory Reactivation)mentioning
confidence: 99%
“…Finally, it can also be caused by the process of memory reconsolidation (especially in the absence of the perpetrator during the first lineup). That is, during the initial lineup some faces of the foils could have similar features as the target, triggering a prediction error, i.e., the mismatch between what is predicted according to previous experiences and what is encountered during re-exposition allowing memory labilization (Forcato et al, 2020). In this case, the memory would be updated during reconsolidation, incorporating erroneous information from the faces present in the lineup into the original memory.…”
Section: Introductionmentioning
confidence: 99%